Comparative study of interruption of signaling pathways in lung epithelial cell by two different Mycobacterium tuberculosis lineages. Issue 4 (7th September 2018) - Hadifar, Shima; Behrouzi, Ava; Fateh, Abolfazl; Khatami, Shohreh; Rahimi Jamnani, Fatemeh; Siadat, Seyed Davar; Vaziri, Farzam
Abstract: Alveolar epithelial cell (AEC) provides a replication niche for Mycobacterium tuberculosis . Based on the role of AEC in M. tuberculosis pathogenesis and existence of genetic diversity within this bacterium, we investigated interactions between AEC II and two different M. tuberculosis lineages. We have compared the transcriptome and cytokines/chemokines levels of A549 infected by M. tuberculosis lineage three and four using qRT‐PCR and ELISA arrays, respectively. We showed different M .  tuberculosis strains induced changes in different effectors that involved in TLRs and NF‐κB signaling pathways. We observed different reaction of the studied lineages specifically in pathogenesis, immune evasion mechanism, IL‐12/IFN‐γ axis, and autophagy. Similar behavior was detected in regarding to apoptosis, necroptosis, anti‐inflammatory responses, and canonical inflammasome. Our findings contribute to elucidate more details in pathogenesis, immune evasion strategies, novel target and druggable pathway for therapeutic intervention, and host directed therapy in tuberculosis infection. Also, different M .  tuberculosis lineages‐dependent host–pathogen interactions suggested using only one strain for this kind of research will be controversial. Abstract : Investigation of interaction between Mycobacterium tuberculosis strain with consideration of its genetic background and alveolar epithelial cell, as a replicative niche for this bacterium, may contribute in improving and developing of tuberculosis diagnostic, prophylactic, and therapeutic methods. We showed different M . tuberculosis strains induced changes in different effectors that involved in TLRs and NF‐κB signaling pathways.